OPTIMASI DESAIN MESIN PENGUPAS KULIT BIJI MELINJO MELALUI PENDEKATAN DESIGN FOR MANUFACTURING AND ASSEMBLY - MUHAMMAD ANDHIKA BINTANG MAHAPUTRA, (2020)
Emping melinjo is an export commodity that has high potential as a source of foreign exchange for the country besides of course in meeting domestic demand. However, making chips that still use hands causes chips productivity tends to be low so that the high demand cannot be matched by the availability of chips produced by chips producers. The purpose of this paper is to develop a design in accordance with the DFMA method so that it simplifies the assembly process and shortens the total assembly time. From the results of the study resulted in a design of the application of DFMA, where there are some changes in accordance with the method, namely simplifying the form of components, then also the process of merging, and eliminating the components that function minimally on the machine structure with the aim of reducing production time and total production costs. The optimized design has dimensions of 370 x 465 x 873.66 mm. The design result of applying DFMA has an assembly efficiency of 3.7%. After optimization, the design with the implementation of DFMA has a total production cost of Rp2,531,000,00.